Vertical jump in female and male volleyball players: a review of observational and experimental studies - Ziv, G.; Lidor, R. (Scandinavian Journal of Medicine & Science in Sports, 2010)
The main purpose of this article was to review a series of studies (n=32; 24 observational and eight experimental) examining vertical jump (VJ) performances in female and male volleyball players. The main findings of this review are (a) players of better performing teams have higher VJ values; (b) strength and conditioning programs that emphasize plyometric training can increase VJ performance; and (c) it is important to continue conditioning sessions throughout the season in order to maintain VJ performance. Three research limitations associated with the testing protocols and the strength and conditioning programs used in the studies were outlined: (a) the use of multiple testing protocols; (b) lack of experimental studies; and (c) lack of data on the effect of VJ performance on achieving success in actual games. Four recommendations for volleyball and strength and conditioning coaches were given: (a) Plyometric training should be included in the annual training program; (b) Interruptions in the conditioning program during the season should be avoided; (c) Overtraining during the pre-season should be avoided; and (d) VJ performance should be tested throughout the entire season.